2011
DOI: 10.1007/s13311-011-0033-5
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte Fate after Spinal Cord Injury

Abstract: Summary: Oligodendrocytes (OLs) are particularly susceptible to the toxicity of the acute lesion environment after spinal cord injury (SCI). They undergo both necrosis and apoptosis acutely, with apoptosis continuing at chronic time points. Loss of OLs causes demyelination and impairs axon function and survival. In parallel, a rapid and protracted OL progenitor cell proliferative response occurs, especially at the lesion borders. Proliferating and migrating OL progenitor cells differentiate into myelinating OL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
157
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(162 citation statements)
references
References 170 publications
(196 reference statements)
0
157
0
Order By: Relevance
“…Neurons and oligodendrocytes are very sensitive to secondary damage after SCI ( [53,54]; [32]). Their death and degeneration in and around the lesion site disrupt neural circuitry and contribute to neurological dysfunction [55].…”
Section: Discussionmentioning
confidence: 99%
“…Neurons and oligodendrocytes are very sensitive to secondary damage after SCI ( [53,54]; [32]). Their death and degeneration in and around the lesion site disrupt neural circuitry and contribute to neurological dysfunction [55].…”
Section: Discussionmentioning
confidence: 99%
“…The result of the secondary wave of cell death leads to a compounded effect on astrocyte and microglial recruitment to the lesion core and penumbra. Furthermore, oxidative stress [88] and axonal degeneration can result in death of oligodendrocyte populations that myelinate the affected axons [89]. The myelin debris left behind by apoptotic oligodendrocytes in addition to that resulting from the initial trauma further exaggerates the unfavorable environment at the lesion site and penumbra.…”
Section: Molecular and Cellular Consequences Of Cns Injury: Implicatimentioning
confidence: 99%
“…In support of this hypothesis, we found increased myelinated white matter chronically after injury in the rat model of contusive SCI, an effect that was associated with significantly improved hind limb function. The phenomenon of remyelination and partial restoration of conduction in demyelinated axons of the adult central nervous system is well established (For review: Almad et al, 2011). Recently, Cao et al (2010) showed that transplanted OPCs expressing CNTF differentiate into mature oligodendrocytes that ensheath demyelinated axons and partially restore conduction after contusive SCI.…”
Section: Proliferation Of Ng2mentioning
confidence: 99%